Meningkatkan Kualitas Hidup Lansia melalui Skrining Pengetahuan Hipertensi dan Program Senam di Posyandu Ngudi Waras Surakarta - Wijayanti; Wianti, Sri; Aseta, Pandu; Hafiduddin (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The elderly population in Indonesia is particularly vulnerable to degenerative diseases such as hypertension, which often remain undiagnosed due to subtle symptoms. Addressing these health challenges is crucial for improving their quality of life, as uncontrolled hypertension can lead to severe complications like stroke and heart disease. Objective: The purpose of this service was to enhance elderly knowledge about hypertension and emphasize the importance of effective blood pressure management, while encouraging active participation in exercise routines. Method: Conducted at Posyandu Ngudi Waras, Surakarta, this program involved health screenings, educational sessions using leaflets, and regular exercise activities. The methodology included stages of socialization, implementation, technology application, evaluation, and sustainability. Result: The program significantly improved participants' knowledge of hypertension, with scores increasing from 53.53 to 82. Blood pressure measurements showed a decrease in systolic pressure from 137 mmHg to 130 mmHg, and diastolic pressure from 88 mmHg to 80 mmHg after exercise. All participants expressed high satisfaction, and participation was at 100%. However, transportation challenges were noted as a barrier. Conclusion: The program at Posyandu Ngudi Waras effectively enhanced the quality of life for the elderly through health education and physical activity. To overcome transportation barriers and ensure broader participation, developing organized transportation support is recommended. Overall, the initiative shows promise in reducing hypertension prevalence and promoting a healthier lifestyle among the elderly.